ArcB1, a Homolog of Escherichia coli ArcB, Regulates Dimethyl Sulfoxide Reduction in Shewanella oneidensis MR-1 - Shroff, Namita P. (American Society for Microbiology (ASM), 2010)
Shewanella oneidensis is a metal reducer that uses the cyclic AMP receptor protein, CRP, to regulate anaerobic respiration. In addition, ArcA(So) is required for anaerobic growth with dimethyl sulfoxide (DMSO) and plays a role in aerobic respiration. The sensor kinase that activates ArcA(So) in S. oneidensis is not known. ArcB1(So), a homolog of the Escherichia coli sensor kinase ArcB(Ec), was identified and found to be required for DMSO reductase gene expression. In combination with HptA, ArcB1(So) complemented an E. coli arcB(Ec) mutant. ArcA(So), ArcB1(So), and HptA appear to constitute a two-component signal transduction system that regulates DMSO reduction in S. oneidensis.